RACIAL PREJUDICE TOWARD THE MAIN CHARACTER ‘DON SHIRLEY’ IN GREEN BOOK FILM - Moch Erik Oktavuari; Nasrullah -; Jonathan Irene Sartika Dewi M. (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
In this thesis, the researcher discusses the racial prejudice in Green Book film. The purposes of this thesis are to identify the types of racial prejudice portrayed in Don Shirley’s character and describe how racial prejudice is portrayed in Don Shirley’s character in the film. The data used in this study were words in the forms of narration, conversation, action, and scene related to the portrayal of racial prejudice towardsDon Shirley’s character who works as a jazz pianist on his tour in the film. In this thesis, the researcher uses the method of qualitative research and a mimetic approach. Further, the theories that are used in analyzing the data, the researcher uses Sergio Romero’s theory about the types of the racial prejudice of the dominant group and Pickering and Hoeper’stheory about character and characterization. The results reveal that Don Shirley experienced all three types of racial prejudice; stereotype, discrimination, and racism. The researcher found there are thirteen data of racial prejudice and the most prominent is discrimination. These are the results representing that Don Shirley’s character is still the object of discrimination despite his social status.